A STUDY ON PUBLIC PROPERTY TAX IN KALABURAGI CITY, KARNATAKA STATE, INDIA (International Journal of Food and Nutritional Sciences, 2022)
In India municipal tax is the most important while collecting Property tax from public. Theoretically, property tax subscribes to efficiency, ability to pay, benefit and equity principles of public finance. However, it is grossly under-exploited. The reasons why the possible of property tax is far from being realized include systemic problems and inefficiency in Kalaburagi municipal tax administration. Considering the importance of property tax is for municipal autonomy and its huge unexploited potential. This paper attempts to look to theory and data analysis, including innovative initiatives launched by Kalaburagi city in India in the past for designing and pursuing a robust agenda of property tax reforms. We suggest municipal reforms with a focus on user charges for measurable services, move to capital value-based property tax with land tax component linked to the market value of land, tax mapping and benchmarking, addressing tax base, exemptions, coverage, valuation and collection efficiency.